Effects of ginseng root saponins and ginsenoside Rb1 on immunity in cold water swim stress mice and rats. - Luo Yun-Man; Cheng Xiu-Juan; Yuan Wen-Xue (Acta Pharmacologica Sinica, 2016)
The proliferation of splenic lymphocytes, the humoral immune response to sheep red blood cells, and the phagocytotic function of intraperitoneal macrophages were all suppressed by cold water (4 degrees C) swim stress (CWSS) for 5 min in rats and for 3 min in mice. Meanwhile, the levels of serum corticosterone increased. Ginseng root saponins 100 mg.kg-1 or ginsenoside Rb1 10 mg.kg-1 ip or ig completely antagonized the immunosuppression induced by CWSS, and inhibited the increase of serum corticosterone in CWSS rats, but increased the level of serum corticosterone further in CWSS mice.